(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents the results of studying the trajectory and energy distributions of scattered Ar+ ions from the surface of black phosphorus at grazing angles of =30 and 70 with the initial energy of E0 =1 keV. It is shown that at large incidence angles ( >7 0 ) it is possible to analyze the appearance of the ion focusing effect by studying the nature and shape of the trajectory of scattered particles. The scattering coefficient and energy of scattered ions reflected from the bottom of the semi-channel and the surface atomic row are calculated. The energy distributions of scattered ions are calculated and it is shown that the peak of the surface atomic row and the bottom of the semichannel merge into one peak, due to the small difference in the energy of these ions, which is explained by the small value of the initial energy of the incident ions.